2013
DOI: 10.23887/jish-undiksha.v2i1.1313
|View full text |Cite
|
Sign up to set email alerts
|

Perbaikan Kondisi Kerja Berbasis Kearifan Lokal Yang Relevan Dengan Konsep Ergonomi Untuk Meningkatkan Kualitas Kesehatan Dan Produktivitas Pematung

Abstract: AbstrakTujuan penelitian ini adalah untuk mengetahui: 1) Peranan Puskesmas dalam Program Pelayanan Kesehatan Peduli Remaja (PKPR); 2) Keterlaksanaan program PKPR terhadap kesehatan reproduksi remaja; 3) Peranan program PKPR terhadap kesehatan reproduksi remaja. Penelitian ini merupakan penelitian deskriptif kualitatif dengan teknik pengumpulan data melalui wawancara, observasi, dan focus group discussion. Informan dipilih secara purposive sampling. Data dianalisis dengan menggunakan analisis interaktif model d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…The reduction in fatigue is physiologically caused by the oxygen supply obtained after active rest and the nutritional intake obtained by the gipang workers. Regarding these findings, several researchers reported that providing adequate and appropriate active rest can reduce fatigue in workers by 17.78% (Puspadewi, et al, 2018); improving working conditions through a total ergonomic approach, namely regulating work attitudes, providing short breaks, and providing tea can reduce worker fatigue from 37.77% to 35.37% (Adiatmika, 2007); giving bananas, short breaks and stretching can reduce worker fatigue in oil palm harvesters by 23.75% (Damantalm, 2018); giving snacks in the form of sweet tea and applying short breaks to odontectomy practitioners in the Department of Dentistry can reduce fatigue 52.73% to 47.00% (Wiradharma, 2012); and the application of active rest to sculptors associated with the culture that is developing in the local community, namely at Tengai Tepet or 12.00 WITA and Sandikala or 18.30 WITA may not do work and are able to improve blood circulation so that resulting in a decrease in fatigue by 11.27% (Sutajaya & Ristiati, 2014). The results of hypothesis testing on work motivation can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in fatigue is physiologically caused by the oxygen supply obtained after active rest and the nutritional intake obtained by the gipang workers. Regarding these findings, several researchers reported that providing adequate and appropriate active rest can reduce fatigue in workers by 17.78% (Puspadewi, et al, 2018); improving working conditions through a total ergonomic approach, namely regulating work attitudes, providing short breaks, and providing tea can reduce worker fatigue from 37.77% to 35.37% (Adiatmika, 2007); giving bananas, short breaks and stretching can reduce worker fatigue in oil palm harvesters by 23.75% (Damantalm, 2018); giving snacks in the form of sweet tea and applying short breaks to odontectomy practitioners in the Department of Dentistry can reduce fatigue 52.73% to 47.00% (Wiradharma, 2012); and the application of active rest to sculptors associated with the culture that is developing in the local community, namely at Tengai Tepet or 12.00 WITA and Sandikala or 18.30 WITA may not do work and are able to improve blood circulation so that resulting in a decrease in fatigue by 11.27% (Sutajaya & Ristiati, 2014). The results of hypothesis testing on work motivation can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The results of identifying VoC from a participatory approach to 5 stakeholders, followed by categorizing customer needs against AT criteria (Surata, 2014). Organizing customer needs according to the characteristics of the machine to be made.…”
Section: Costomer Needsmentioning
confidence: 99%
“…Changes in machine design have consequences for changes in the UI system to increase the ability to monitor and control process parameters during pasteurization (Stone et al, 2005). The redesign of the pasteurization machine uses PEF technology to provide significant value that the UI design and system is considered through several appropriate technology (AT) criteria including technical, economic, ergonomic, efficiency, environmental, trends, and sociocultural (Surata, 2014). With the emergence of several alternative development redesigns for pasteurization machines (Ulrich & Epingger, 2020), it is necessary to select alternative designs using Pugh's method (Burge, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pendidikan kesehatan reproduksi sangat penting bagi remaja karena dapat meningkatkan pengetahuan dan sikap remaja agar mereka memiliki kesadaran dan tanggungjawab yang tinggi terhadap kesehatan reproduksinya. Hal ini sesuai dengan Sutajaya (2013), yang menyatakan bahwa pendidikan kesehatan reproduksi dan seksualitas memiliki tujuan utama untuk memberikan informasi kepada remaja untuk memberdayakan mereka dalam membangun nilai dan keterampilan berelasi yang memampukan mereka membuat keputusan yang bertanggung jawab untuk menjadi orang dewasa yang sehat secara seksual pendidikan kesehatan reproduksi dan seksual penting untuk di berikan.…”
Section: Pendahuluanunclassified